Old Testament Theology and the Canon - Goldingay, John (Tyndale bulletin, 2008)
The article argues that Old Testament theology considers the insight that emerges from the form of the Old Testament canon, that it focuses on the canon of the Old Testament itself not the history of Israel, that it lets the canon itself be the canon, that it nevertheless recognises a canon within the canon, that it treats the first part of the twofold canon as of significance in its own right, but that it expects to find that the two parts of this canon illumine each other.